The rise of antifeminist perspectives among future educators: a growing concern? - Idoiaga-Mondragon, Nahia; Legorburu Fernandez, Idoia; Picaza Gorrotxategi, Maitane; Alonso Saez, Israel (Frontiers in Psychology, 2025)
IntroductionAntifeminist discourses have historically emerged in response to feminist advancements. In Spain, the past decade has seen significant feminist progress, yet antifeminist rhetoric has simultaneously gained traction, particularly among younger populations. This study examines the antifeminist narratives present among university students in education programs, a critical demographic as future educators play a key role in shaping social attitudes.MethodsA free association exercise was conducted with 252 students enrolled in education programs. The collected textual data were analyzed using Iramuteq software, applying lexical analysis techniques to identify dominant antifeminist discourses.ResultsThe findings indicate that the most prominent antifeminist narratives among participants center on feminist principles, salary aspirations, perceived disparities in rights, household chores, and the alleged provocative behavior of women. Notably, frequently cited statements include “Feminism does not seek equality” and “They expect to be paid the same”, reflecting common misconceptions about feminism. Despite expressing support for gender equality, participants were less likely to self-identify as feminists.DiscussionThese findings highlight the contradictions within young adults' perceptions of feminism and gender equality. The persistence of antifeminist narratives within future educators underscores the need to address these discourses in academic settings. Integrating feminist pedagogies into teacher training programs is essential to fostering a more equitable and informed educational environment.ConclusionThis study underscores the necessity of actively confronting antifeminist rhetoric within educational institutions to ensure that future educators contribute to gender equality rather than perpetuate misconceptions.